Partnerships at the interface of education and mental health services: the utilisation and acceptability of the provision of specialist liaison and teacher skills training - Fazel, M; Soneson, E; Sellars, E; Butler, G; Stein, A (MDPI, 2023)
Partnerships between school staff and mental health professionals have the potential to improve access to mental health support for students, but uncertainty remains regarding whether and how they work in practice. We report on two pilot projects aimed at understanding the implementation drivers of tailored strategies for supporting and engaging front-line school staff in student mental health. The first project provided regular, accessible mental health professionals with whom school staff could meet and discuss individual or systemic mental health concerns (a school ‘InReach’ service), and the other offered a short skills training programme on commonly used psychotherapeutic techniques (the School Mental Health Toolbox; SMHT). The findings from the activity of 15 InReach workers over 3 years and 105 individuals who attended the SMHT training demonstrate that school staff made good use of these services. The InReach workers reported more than 1200 activities in schools (notably in providing specialist advice and support, especially for anxiety and emotional difficulties), whilst most SMHT training attendees reported the utilisation of the tools (in particular, supporting better sleep and relaxation techniques). The measures of acceptability and the possible impacts of the two services were also positive. These pilot studies suggest that investment into partnerships at the interface of education and mental health services can improve the availability of mental health support to students.